The Policies of the Soviet Union and the European Members of the North Atlantic Alliance Toward NATO - Lampson, Edward T. (Library of Congress. Congressional Research Service., 1972)
This report discusses the policies of the Soviet Union and the major European members of NATO towards the organization and evaluates the commitment levels of the European members of NATO.